Parents’ online self-disclosure and parental social media trusteeship - Thorsten Naab (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2019)
Although parents consider online privacy important, they insouciantly include personal information about their children. Reviewing research on the privacy paradox and online self-disclosure, this article suggests the concept of media trusteeship as an additional theoretical perspective to understand how parents shape the digital identity of their children. The results of 46 in-depth interviews indicate that parents are largely unaware of the described role duality and are only partially able to foresee the consequences of their activities. The analysis identifies three distinct types of parental media trusteeship: While some parents shield their offspring from social media, others appear unable to respond adequately to the risks of social media activities or seem to ignore them completely. Finally, it became clear that the parents surveyed had no idea how to teach media literacy and guide their children to a safe and careful use of social media.